Fat but Fit: How physical fitness can mitigate the cardiovascular risks of obesity? - Zara Khalid; Furqan Ahmed Siddiqi; Tahira Sadiq; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Obesity has long been recognized as a major independent risk factor for cardiovascular diseases (CVD). However, intriguing paradoxes such as the "obesity paradox" and the "fat but fit" phenomenon have been associated with it. The "fat but fit" paradigm suggests that overweight or obese individuals might face a lower risk of developing cardiovascular disease if they possess high levels of physical fitness. In other words, higher fitness levels may mitigate the negative impact of obesity on cardiovascular risk, leading to a reduction in overall mortality due to CVD. The evidence surrounding this paradox is conflicting, highlighting the necessity for further research. The complex relationship between physical fitness, obesity, and cardiometabolic health is influenced by individual and environmental factors. Consequently, it becomes imperative to conduct more studies to comprehend this intricate interplay fully. To address this issue, it is important to focus on formulating strategies that promote the maintenance and enhancement of cardiorespiratory fitness in overweight and obese individuals. Moreover, including fitness evaluations in comprehensive risk stratification can significantly improve clinical decision-making. Keywords: Cardiovascular diseases, obesity, obesity paradox, physical fitness.